Written language learning: an analysis of the impact of Emergency Remote Teaching - Araújo, Rute Santos; Souza, Brenda Kessia Arruda de (Entrepalavras, 2025)
In 2020, with the Covid-19 pandemic, Emergency Remote Teaching (ERE) needed to be implemented in Brazil in order to reduce the learning gap that was about to occur. Although measures have been taken, it was noticed that students had learning difficulties in the pandemic period, but ERE controls in later stages of education still need to be investigated. Thus, aware that it is relevant to analyze how the level of students is like in a post-pandemic period, this study proposes to investigate how much remote teaching interfered in the acquisition of written language by students of elementary school. The theoretical-methodological perspective adopted is based on the theory of writing psychology substantiated by Ferreiro and Teberosky (1999). The data we obtained for the research had the participation of 41 students from the 1st year of elementary school of a public school, arranged in two groups: (i) 2019 students and (ii) 2022 students, these students carried out a survey evaluation of writing, which is based on the studies of Ferreiro and Teberosky (1999). In comparative terms, data analyzes suggest that the students of 2022 were even more below of the desirable level than the students of 2019 in terms of acquisition of the language's written system, showing that the implementation of the ERE, during the pandemic brought losses to the teaching-learning process.